Territorialidades da agricultura orgânica e da agroecologia na microrregião de Erechim/RS a partir das ações socioambientais do CAPA e do CETAP - Gaboardi, Shaiane Carla (2017)
In Brazil, mainly after the 1960's, the technical and economic basis of agriculture has changed, connected to the technical and scientific precepts of the Green Revolution, which was linked to the developmental doctrine and to a speech of agriculture modernization. The Green Revolution induced a process of productive specialization and the dissemination of entrepreneurship based on the agro-export economy, in addition to a strong dependency of products controlled by great agro-industrial complexes, such as agrochemicals and agricultural machinery. Capitalist relations in on countryside was intensified after this period, generating many social and environmental impacts. Thereafter, social movements and popular organizations started questioning and contesting the harmful effects of agriculture modernization. Among these movements, in the Microregion of Erechim, located in the north of the state of Rio Grande do Sul, two non-governmental organizations which operate since the 1980's can be highlighted: the Center for Support and Promotion of Agroecology (CAPA) and the Center for Popular Alternative Technologies (CETAP). On this master’s dissertation, we aim at analyzing the actions that support organic agriculture and agroecology developed by the CAPA and the CETAP on the Microregion of Erechim, with emphasis on those focused on environmental conservation. Therefore, the methodological procedures were based on three main axes: 1) Literature review, which includes issues about nature, development, organic agriculture and also agroecology; 2) Data collection and systematization at the Brazilian Institute of Geography and Statistics (IBGE) and at the Economics and Statistics Foundation of Rio Grande do Sul (FEE), in order to characterize the land distribution, the population dynamics, and mainly, data about land use; 3) Field studies and interviews with employees of both of the NGOs and in family units assisted by them. The particular characteristics and the complexity of the reality make the actions of these two organizations take place beyond environmental aspects. At the same time that these NGOs promote conservation and preservation of the environment seeking the sustainability of agrosystems, they also focus on economic (commercialization and certification), cultural (traditional knowledge) and political aspects (lack of technical support and of specific public policies) which involve the agroecology theme. The starting point of the most successful experiences found on our research was through the practice of organic agriculture as an alternative income. Nevertheless, in the course of time, with the agroecological transition, other aspects of the farmers' lives started to be considered, such as health, satisfaction, gender issues, rescue of the cultural dimension, natural resources conservation, among others, which have evoked and keep evoking the protagonism and the existence of the farmers involved in the projects of the institutions.